History, Memory, and Messianic Politics in Walter Benjamin: A particular experience from the past - Suárez Gómez, Jorge Eduardo (2025)
The German Jewish literary critic Walter Benjamin outlined in his last text “On the Concept of History”, a heterodox conceptual relationship between history and memory. To this end, from the beginning of his career, he engaged in a dialogue between intellectual traditions that seemed contradictory to some of his contemporaries. The aim is to understand how he articulated elements of these perspectives to propose that way of understanding and experiencing the past between history and memory through messianic politics.